A study of Donor Deferrals in Sbksmi & RC Tertiary Health Care Centre in Gujarat. - DR. PRASHANT KUMAR; DR. ASHU DOGRA (International Journal of Pharma and Bio Sciences, 2018)
The blood donor is the key to patient safety.Donor screening criteria are established to protect both donors and recipients. To ensure blood safety, safe donors need to be recruited and high-risk donors should be discouraged from donation. The ideal blood donor is a voluntary non-remunerated repeat donor, as this donor will have the lowest risk of having an infection that may be transmitted through blood transfusion. The study was conducted at SBKSMI & RC Medical college hospital blood bank from January 2013 to January 2016 with prior permission from the head of the concerned department. Most common cause for deferral was underweight in both male and female donors and the commonest cause among permanent deferral was donor being diabetic and on insulin. The next common cause was anemia. The rate and reasons of deferral differs from region to region and one center to the other. To protect blood donors and recipients, stringent donor screening criteria are necessary. The present study has prompted to make certain recommendations to prevent deferrals to increase the nation's blood supply.Donation criteria must be explained to the donors.We should always explain about the confidentiality of donor before asking any history as the donor will not hesitate in giving the answers of the questions asked by the physician.In planning blood donor recruitment programs is always helped by understanding the deferral reasons and rates and an estimate can be made of real blood donors pool which are not the same when we consider the blood donor pool. We must educate the donors regarding donation criteria. Physicians must give donors assurances regarding the confidentiality of donor selection so that potential donors answer the questions honestly. Understanding the rates and reasons for deferral can help in planning recruitment programs and in obtaining more accurate estimates of the real eligible blood donor pool, which may vary considerably from the potential blood donor pool. The donor deferral can be reduced by providing information and educating the donors.